Research recast(ed): S2E18 - Student Research Day: student research spotlight - Katryna Yasinski, Madison Karpiak, and Amy Wildeman - Miskiman, Megan; Schabert, Reinette; Yasinski, Katryna; Karpiak, Madison; Wildeman, Amy (My University, 2023)
In today’s episode, we are joined by three student researchers here at MacEwan: Katryna Yasinski from the Faculty of Fine Arts and Communications, Madison Karpiak from the Faculty of Arts and Science, and Amy Wildeman from the Faculty of Nursing.
Keywords: fashion; relationships to clothing; sexual violence perpetrators; risk assessment; healthcare providers; body art; client perceptions